(3GdCLhHI GdeQVjI Yf GdCSFdI GdfMhjIs - (3eMeO Hf eMeO Hf eMeO Hf ESeGYjd GdQGYj GdCfOdSj, GdQGYj,J (B853 (3g` s ((3EHQGgje Hf eUWai Hf ESeGYjd s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd efGW GdYde UMI Gdage hMSf GdOQGjI, hde jLYdg dG HWhd GTJZGd hdG HcKQI QhGjI, hEfeG LdYg fhQG hgOi s
(3BNQgG (B:s
(3hGdMeO ddg hMOg, hUdi Gddg Ydi SjOfG eMeO hBdg hCUMGHg hSde JSdjeG s
(3GdfSNI HgG MhGTs
(3cJHJ GdYfhGfGJ HGdeOGO GdCMeQs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B276s
Keywords: (3GdfMhs